2013
DOI: 10.1037/a0033599
|View full text |Cite
|
Sign up to set email alerts
|

Motor demands impact speed of information processing in autism spectrum disorders.

Abstract: Objective The apparent contradiction between preserved or even enhanced perceptual processing speed on inspection time tasks in autism spectrum disorders (ASD) and impaired performance on complex processing speed tasks that require motor output (e.g. Wechsler Processing Speed Index) has not yet been systematically investigated. This study investigates whether adding motor output demands to an inspection time task impairs ASD performance compared to that of typically developing control (TDC) children. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…In addition, the inspection time studies included children with ASD (Scheuffgen et al 2000; Wallace et al 2009; Kenworthy et al 2013), or a broad range of ages from adolescence and adulthood (Barbeau et al 2013), whereas the current study focused on adults with ASD. There may be a developmental change or delay (Williams et al 2013) in processing speed in ASD, which could also explain the discrepancy in results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the inspection time studies included children with ASD (Scheuffgen et al 2000; Wallace et al 2009; Kenworthy et al 2013), or a broad range of ages from adolescence and adulthood (Barbeau et al 2013), whereas the current study focused on adults with ASD. There may be a developmental change or delay (Williams et al 2013) in processing speed in ASD, which could also explain the discrepancy in results.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of investigations have provided evidence of significant reductions in processing speed in both children (Oliveras-Rentas et al 2012; Nader et al 2015; Hedvall et al 2013; Mayes and Calhoun 2007; Bavin et al 2016a, b) and in adults with ASD without comorbid ID (Holdnack et al 2011; Faja et al 2009; Eack et al 2013a), and several studies showed relationships between slower processing speed and impaired measures of social cognition (Oliveras-Rentas et al 2012; Lerner et al 2013). However, there are several studies that do not show reduced processing speed in children with ASD (Scheuffgen et al 2000; Wallace et al 2009; Kenworthy et al 2013), and even fewer that examine the presence of this impairment in adulthood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, normal appearing activation patterns emerged by the second scan, at which point the ASD group attained the same level of activation that was observed by the controls in the first scan. This suggests that the individuals with ASD may engage in slower, inefficient information processing (Bertone et al 2005; Dawson et al 2005), which may have been compounded by the simple motor response included in our paradigm (Kenworthy et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Increased activation in the putamen in the adolescent ASD group may reflect a compensatory process in order to overcome possible delayed development in cortical (i.e., FEF) control in order to generate a successful AS response. There is little fMRI evidence showing activation differences in putamen in ASD, with one study linking reduced activation in putamen with repetitive behavior symptoms and verbal fluency in ASD [Kenworthy et al, 2013]. However, converging lines of research from PET and structural MRI have suggested that the putamen may be a locus of dysfunction in ASD.…”
Section: Discussionmentioning
confidence: 99%